Investigação das propriedades magnetoelásticas da ferrita de níquel : análise teórico-experimental - Afonso, Ricardo (2018)
In this dissertation, we investigate the magnetoelastic properties of nickel ferrite compared to the pure metal nickel, either by ab-initio calculation or through experiments using the capactive cell technique. The first step of our approach is to establish the convergence criteria on density functional theory (DFT). This also required us to benchmark our method by using other materials such as pure Fe, Co and diamond. The first step of our study is to explore not only the approach of DFT but also its capacity to describe other properties. Since all the electronic structures of theses material have been suitably reported, the second step of our calculation demonstrates how close to the experimental data DFT may result the elastic constants. The results has shown reasonably error to the actual values. On the third moment, our investigation resides to find the magnetostriction coefficient through DFT, which met in accordance with the experiments we carried out using the capacitance technique.